Impact of disuse muscular atrophy on the compound muscle action potential. Issue 1 (17th October 2019) - Mobach, Theo; Brooks, John; Breiner, Ari; Warman‐Chardon, Jodi; Papp, Steven; Gammon, Braden; Nandedkar, Sanjeev D.; Bourque, Pierre R.
Abstract: Background: Disuse atrophy from immobilization is the result of decreased neural activity and muscle unloading. Methods: We studied the impact of disuse on hand intrinsic compound muscle action potentials (CMAPs) in a cohort of 39 patients with unilateral 6‐week immobilization of the hand in a cast, after distal radius fracture. We excluded patients with nerve injury. We compared side‐to‐side CMAP characteristics at the time of cast removal and at a subsequent follow‐up visit, after a mean interval of 7.8 weeks. Results: Statistically significant reductions in CMAP amplitude were noted for the abductor pollicis brevis (29.2%), abductor digiti minimi (19.0%), and first dorsal interosseus (24.9%). There was partial repair of the relative CMAP reduction at the follow‐up visit (20.1%, 10.7%, and 8.7%, respectively). There was no significant change in CMAP duration. Conclusions: These results provide a framework for quantifying the degree of hand intrinsic CMAP amplitude reduction attributed to disuse.